Intrahepatic eosinophilic proliferative phlebitis in Japanese black cattle indicate allergies involving mast cell tryptase-dependent activation - Konnai, Masaki; Takahashi, Kimimasa; Machida, Yukino; Michishita, Masaki; Ohkusu-Tsukada, Kozo (Frontiers in Veterinary Science, 2022)
Cow-specific feature hepatic lesion, termed as eosinophilic proliferative phlebitis (EPP), has been mainly detected in Japanese black cattle and identified histologically eosinophilic infiltration and endothelial hyperplasia in portal areas. We previously proposed EPP as a food allergy from the pathological characteristics and a significant increase of serum immunoglobulin E specific to curly dock (Rumex crispus) in allergens testing, however, first report had regarded EPP an atypical type of bovine fascioliasis. In EPP lesions, eosinophilic infiltration was observed to the hypertrophic endothelium and not to the intrahepatic bile duct, and that was related to eotaxin-1 expression. In EPP, the mast cells increased as well as fascioliasis, and the mast cells producing tryptase without chymase increased with interleukin-4 production. In this context, hyperplasia of periendothelium expressing proteinase-activated receptor-2 (PAR-2) and not angiotensin II was observed. Contrastably, in fascioliasis, unique mast cells producing neither tryptase nor chymase infiltrated, and the periendothelium expressed neither PAR-2 nor angiotensin II. Interestingly, EPP had not occurred liver injury with raised hepatic enzymes like fascioliasis, and suggested to a correlation with severe serum hypo-vitamin A. Overall, this study suggests that EPP is an allergic disease by main difference between adaptive immunity to allergens and innate immunity to parasites.